Of suffering or the insufficiency of the education ‘the decline of the reason and the imposture of the autonomy’ (2013)
The insufficiency of the education is the matter of the present article. That is, the education moves us aside the world, from the elan, and puts us in other world, other elan. The education is a surface that becomes a limit even in the suffering. At least in our West, education, as it is understood and practiced, overlooks the deepest of the being, its suffering, its happiness, its flowering. This could be explaining since education, as the territory of reason, is only concerning to teach to know, to submit Knowledge, to control the soul, to move the being aside that, constituting it as the being-there.